IT governance : policies & procedures - Wallace, Michael; Webber, Larry (Austin : Wolters Kluwer, 2012)
IT Governance Policies and Procedures, 2013 Edition is the premier decision-making reference to help you devise an information systems policy and procedure program uniquely tailored to the needs of your organization.Not only does it provide extensive sample policies, but this valuable resource gives you the information you need to develop useful and effective policies for your unique environment. IT Governance Policies and Procedures provides fingertip access to the information you need on: Policy and planning, Documentation Systems analysis and design.
Includes index.
oif 18/09/14
Loan
Keywords: Information technology; Information technology; Management information systems; Communication in organizations